IMPLEMENTASI PEMBELAJARAN TAHFIDZUL QUR'AN SEBAGAI PROGRAM UNGGULAN DI SMA DARUTTAQWA DAHANREJO KEBOMAS GRESIK (STUDI KASUS TANTANGAN DAN HAMBATAN SISWA DALAM PROGRAM TAHFIDZUL QUR'AN) - Pengelola, Pengelola; Pratama, Muhammad Rusfiansyah (LPPM STAI Ihyaul Ulum Gresik, 2025)
This study explores the implementation of Quran Memorization Learning as a Leading Program at SMA Daruttaqwa Dahanrejo Kebomas Gresik, focusing on the challenges and obstacles faced by students in the program. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews with students, teachers, and administrative staff, as well as direct observation of the Quran memorization learning process. The results of the data analysis indicate various challenges and obstacles faced in implementing the Quran memorization program at SMA Daruttaqwa. One of the main challenges identified is the lack of student motivation to participate in the Quran memorization program. Lack of understanding of the importance of memorizing the Quran, the demands of a dense curriculum, and disturbances from the surrounding environment are contributing factors. In addition, other obstacles include a lack of support from parents and the availability of adequate facilities for Quran memorization learning. Efforts to overcome this include creating a conducive learning environment, providing continuous motivation and support to students, and using interactive and enjoyable learning methods. Collaboration with related parties, such as parents and local communities, is also part of the strategy to overcome challenges and obstacles in the tahfidzul Qur'an program.